Penguatan Balai Latihan Kerja untuk Peningkatan Kualitas SDM Berbasis Kompetensi - RM. Moch. Wispandono; Hadi Purnomo (Penerbit Goodwood, 2024)
Purpose: The aim of this study is to provide an alternative solution for strengthening competency-based BLK in Bangkalan, which is directed at improving the quality of human resources, especially rural human resources. Methodology: This study employed a qualitative method with a descriptive design. A snowball sampling technique was used to determine the informants. Data were collected using in-depth interviews, observations, and literature. Content analysis was used to identify patterns and themes. Results: Eight aspects must be fulfilled to realize competency-based institutional strengthening: work competencies, curriculum, training materials, management or administration of work institutions, instructors and training personnel, facilities, and infrastructure. Financial Administration and Valuation. Conclusions: Based on the results of the study, it turns out that there are several aspects that still need attention for institutional strengthening. These aspects are: (1) the condition of training facilities and infrastructure, especially for the field of mechanical engineering vocational, (2) increasing the number of instructors which is still lacking compared to the number of students taking part in training (3) increasing instructor competence where instructors need to have methodological and technical competence as evidenced by a competency certificate that must be owned.Limitations: This study examined only the BLK strengthening variable in increasing workforce competency. It is possible that further studies could develop more aspects of strengthening BLK to produce a competent workforce.Contribution: This could address the problem of unemployment and improve social welfare in the community.